Attitude toward teamwork and work engagement as predictors of job satisfaction in nurses: a cross-sectional study - Ana J. Cayllahua Curiñaupa; Yessica S. Rojas Palma; Mayela Cajachagua Castro; Salomon Huancahuire-Vega (BMC Nursing)
Abstract Background Nurses are important members of health institutions since their participation influences the quality of service. Identifying the behavior of the variables studied will favor the development of strategies to strengthen management, which will result in improving the quality of nursing care. This study seeks to identify whether attitude toward teamwork and work engagement are predictors of nurses’ job satisfaction. Methods Cross-sectional study involving 329 nursing professionals providing direct patient care in a public hospital. The data collection period was from January to July 2022. The T-TAQ questionnaire, the Utrecht Work Engagement Scale (UWES-17) and the SL-SPC Opinion Scale were used to evaluate the attitude towards teamwork, the engagement, and job satisfaction, respectively. The data was analyzed using descriptive statistics, bivariate analysis with Chi-square, and multivariate analysis with binary logistic regression (95% CI and p < 0.05). This study followed the recommendations of the STROBE to ensure adequate and complete reporting of cross-sectional studies. Results A relationship was found between the time working in the institution (p = 0.005), the area of work (p = 0.005), attitudes towards work teams (p = 0.000), and engagement (p = 0.000) with job satisfaction. The multivariate analysis showed that nurses who have worked in the institution for more than 5 years (OR: 3.328; 95% CI: 1.741–6.364), who have a positive attitude towards work teams (OR: 9.881; 95% CI: 4.321) -22.594) and have a high work engagement (OR: 10.764; 95% CI: 4.745–24.414) have a greater probability of expressing high job satisfaction. Conclusion The time spent working in the institution, attitude towards teamwork, and work engagement are predictors of job satisfaction and key factors in nursing professionals’ work. Effective interventions to enhance work commitment and teamwork include recognition and reward systems, personalized incentives, a positive work environment, and integration activities promoting communication. Strong leadership and active listening ensure employees feel valued, fostering motivation, engagement, and collaboration within the team. Clinical trial number Not applicable.